SPEECH ACTS CONTAINED IN ENGLISH MODAL VERB WILLAND INDONESIAN ADVERB AKANIN BUSH’S AND SBY’S VICTORY SPEECHES AS ELECTED PRESIDENTS - Nurlaila, Nurlaila (Prosiding PESAT, 2013)
This is a contrastive study comparing the use of English modal verb will in Bush’s victory speech with the use of Indonesian adverb akan in SBY’s victory speech. The aims of this study are (1) to indentify type of speech actscontained in the English modal verb will in Bush’s speech and in the Indonesian adverb akan in SBY’s speech; (2) to identify percentage of the use of speech acts contained in the English modal verb will as well as Indonesian adverb akan, and; (3) to identify tendency of the use of direct speech act and indirect speech act through the use of English modal verb will and Indonesian adverb akan by Bush and SBY. To achieve the aims of this study, the researcher employs the descriptive analytical method and critical discourse analysis approach. The results of this study show that (1) Bush employed English modal verb will to express directive speech act in the form of invitation as well as assertives speech act in the form of assertion, prediction, and statement, while SBY employed Indonesian adverb akan to express commissives speech act in the form of promise as well as declarative speech act in the form of declaration; (2) 50% of the English modal verb will employed by Bush functions to express directives speech act and the remaining 50% functions to express assertives speech act, whereas 94% of the Indonesian adverb akan employed by SBY functions to express commissives speech act and the remaining 6% functions to express declaratives speech act; (3) Bush tended to express the meaning of his utterance through direct speech act in which 87% of his utterance is delivered by direct speech act and the remaining 13% is delivered by indirect speech act while SBY delivered his all (100%) utterance meaning by direct speech act.